Studi Tentang Figur Pendidik Dalam Hadis - Handayana, Sri (MKKS SMA, MKKS SMP se-Kota Metro, Persatuan Sarjana Pendidikan Islam Wilayah Provinsi Lampung, dan CV.IQRO Penerbitan, 2017)
In general, educators are all parties who are obliged to nurture and educate for someone to grow and grow naturally. Educators hold a central position in determining the success of teaching and learning process. Therefore, educators must have competencies: (a) personality competence; (b) pedagogic competencies such as understanding the physical and mental condition of learners, (c) professional competence in the form of mastery and practice of knowledge, and (d) social competence that is the ability of educators to interact effectively with the participants Educators, fellow educators, education personnel, parents/ guardians of students, and the surrounding community.